ORGANIZING INDEPENDENT ACTIVITIES IN MUSIC EDUCATION THROUGH BLENDED LEARNING - Bobokulova Moxinur Jamshid qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the organization of independent activities in music education using blended learning. The study examines how combining traditional classroom instruction with digital resources and online platforms can enhance students’ self-directed learning, technical skills, and creative development. The article also discusses strategies for integrating blended learning into independent study, fostering active engagement, reflective practice, and professional competencies in music students. The findings demonstrate the effectiveness of blended learning in providing interactive, flexible, and personalized learning experiences that promote both theoretical knowledge and practical skills.